Klim Churyumov: "I Always Repeat that I am Ukrainian. For Me it is a Matter of Principle" - Sergiy Zrazhevskuy (International Society of Philosophy and Cosmology, 2015)
In this article the author reports aboutthe round table "Klim Churyumov - Person of the Century" which held at the Hryhoriy Skovoroda State Pedagogical University of Pereyaslav-Khmelnytsky on April 29, 2015. Klim Churyumov is a Ukrainian world famous astrophysicist, discoverer of Churyumov-Gerasimenko comet (1969) and Churyumov-Solodovnikov comet (1986), director of the Kiev planetarium and corresponding member of National Academy of Sciences of Ukraine. Within a framework of the round table exhibition, information and art displays were introduced for participants' consideration in the library of the University, among which is Art Opening Day "Space far and near." Valeriy Khomich, Klim Churyumov, Galina Zhelezniak, Olga Shkira, Оleg Bazaluk etc. gave reports. At the end of the round table participants and guests of scientific meeting visited National Museum of Space History at the ethnographic village "Pereyaslav".